A Bibliometric Review of Research Developments on Writing Instructional Materials in Indonesian Language Learning at The Higher Education Level - Zulfadhli, Muhammad; Farokhah, Laely; Lakawa, Agustin Rebecca; Dinihari, Yulian; Hamdani, Haris (WASPADA (Jurnal Wawasan Pengembangan Pendidikan), 2025)
This study aims to analyze research trends on writing skills learning materials in Indonesianlanguage learning in higher education through bibliometric analysis using VOSviewer software. This studyuses a bibliometric analysis method. Data were obtained through Publish or Perish to obtain metadata sourcedfrom Google Scholar between 2010 and 2025. Furthermore, the data were analyzed based on quantity,quality, and structure indicators using the VOSviewer. The results show that from 2015 to 2025, researchtrends on writing skills learning materials in Indonesian language learning in higher education experienced asignificant increase. Although in 2022 and 2025 there was a decline. Network visualization throughVOSviewer shows that the most frequently appearing terms are Indonesian language, learning material,student, and university, while research specifically discussing writing learning materials in Indonesianlanguage learning is still very limited. Articles with the highest citations emphasize learning media andlanguage teaching materials in general. These findings indicate a research gap as well as an opportunity forfurther research to develop teaching materials on writing topics that are more innovative and relevant to theneeds of Indonesian language learning in higher education.Keywords: Bibliometrics, Indonesian Language Learning, Learning Materials, Trends, VOSviewer